Regulation of Yki/Yap subcellular localization and Hpo signaling by a nuclear kinase PRP4K - Yong suk Cho (Nature Portfolio, 2018)
The Hippo signaling pathway controls tissue growth by regulating the subcellular localization of Yorkie /Yap. Here the authors show that PRP4K, a kinase involved in mRNA splicing, phosphorylates Yki/Yap in the nucleus, which prevents its nuclear accumulation and inhibits Hippo signaling.